An optimisation of critical quality attributes for acyclovir dispersible tablets: a quality by design approach. (26th February 2021) - Nandedkar, Janhavi; Masane, Manish; Mali, Ashwin J.
The objective of the present study is the development of dispersible tablets (DTs) of an acyclovir (ACV) by quality by design (QbD) approach using maize starch ( X 1 ), sodium starch glycolate ( X 2 ) and magnesium stearate ( X 3 ) as a critical quality attributes (CQA's). The design of experiment (DoE) comprising two levels, three factors (2 3 ) is applied to optimise the combined effect of CQA's on the dependent variables such as disintegration time ( Y 1 ), hardness ( Y 2 ) and drug release ( Y 3, Y 4 and Y 5 ). The centre point batch F5 has depicted the excellent properties comprising 1.20% of X 1, 4.89% of X 2 and 1% of X 3 with better Y 1 (48 ± 1.62 sec), Y 2 (138 ± 1.7 N) and Y 4 (101 ± 1.32%) as compared to the commercial formulation Zovirax©. The key effects of CQA's are observed on the Y 1 and Y 4 (p < 0.05) as compared to the Y 2 of DTs.